Topic modelling of authentication events in an enterprise computer network - Heard,NA; Palla,K; Skoularidou,M (IEEE, 2016)
The possibility for theft or misuse of legitimate user credentials is a potential cyber-security weakness in any enterprise computer network which is almost impossible to eradicate. However, by monitoring the network traffic patterns, it can be possible to detect misuse of credentials. This article presents an initial investigation into deconvolving the mixture behaviour of several individuals within a network, to see if individual users can be identified. Towards that, a technique used for document classification is deployed, the Latent Dirichlet allocation model. A pilot study is conducted on authentication events taken from real data from the enterprise network of Los Alamos National Laboratory.